Técnica de criação e aspectos do parasitismo de Opius sp. (Hymenoptera: Braconidae) sobre a mosca-minadora, Liriomyza trifolii (Diptera: Agromyzidae), em meloeiro - Silva, Roberta Kélia Bezerra (2008)
The leafminer Liriomyza trifolii is nowadays the main pest of melon orchards in the region of Chapada do Apodi, Northeast of Brazil. In order of the high infestation level of this insect, the control based only in pesticides has not been plenty satisfactory. However, considerable parasitism levels occasioned by Opius sp. have been found in field, mainly in the beginning of the production. Because of this fact, the first studies with this parasitoid are been developed in the Entomology Laboratory of UFERSA. The present study had the objective of adapting a rearing technique to the parasitoid Opius sp. in laboratory conditions, and study the aspects of it s parasitism, aiming the future utilization of this parasitoid in the leafminer integrated management programs, in the Semi-Arid conditions of Rio Grande do Norte State. Initially, infested melon leaves with L. trifolii larvae were collected in field to obtain the parasitoids. From the first parasitoids obtained from field, a technique to multiply them in L. trifolii on melon plants was developed. In the observations of the parasitism aspects of Opius sp., was perceived that it prefer to oviposite in 2nd and 3rd instar larvae. In addition, was observed that females present the highest levels of parasitism in the first two days of life